CULTURAL TOURISM STUDENTS’ PERCEPTION ON CONTEXTUAL LEARNING IN ENGLISH TOUR GUIDING CLASS - Md. Yudyantara Risadi (UHN IGB Sugriwa Denpasar, 2024)
This research aimed to analyze the students’ perception on contextual learning in English tour guiding class. The objectives of the research were (1) to investigate students’ perception of contextual learning in tour guiding class, (2) to figure out the implications of contextual learning in students’ tour guiding activity. This research was conducted online for students at State Hindu University I Gusti Bagus Sugriwa Denpasar. The data was collected from the questionnaire through google form and was shared online. the result of the study showed that the quantitative data revealed that participants had positive perceptions toward contextual learning in English tour guiding class. For instance, most of them agree that contextual learning activities, such as site visits and cultural immersion experiences, enhance students’ understanding of English tour guiding concepts. Then, field trips to cultural heritage sites (contextual) allow students to apply theoretical knowledge in real-world settings and enhance my practical skills as a tour guide. Lastly, they believe that contextual learning plays a crucial role in preparing me for a career in cultural tourism as an English tour guide.